A comparative analysis of the income tax provisions applied to outsourced services to South Africa and India - Parshotam, Sandhya Janti (My University, 2017)
This report discusses how the outsourcing of services results in the creation of a service permanent establishment for a non-resident entity. The tax consequences that result from a service permanent establishment in South Africa and India, as the outsourced destinations, will be compared against each other. To remain globally competitive and to provide the best quality of work to clients, entities may decide to outsource services through a secondment arrangement or through a subcontracting arrangement, each having different tax implications. The parties must clearly indicate the type of arrangement in a contractual agreement, as an entity could create a service permanent establishment in a foreign jurisdiction. Non-resident entities often outsource services to organisations in South Africa and India. This report provides a comparative analysis of the income tax provisions applicable to a resident and a non-resident for both a company and individual in South Africa and India. It further analyses income tax provisions related to the definitions related to residency, for a company and an individual in terms of the Income Tax Act 58 of 1962 in South Africa and the Incometax Act, 1961 in India. Other provisions compared in this report include the tax rates, rebates and thresholds in terms of such legislation. Key Words: Non-resident, Resident, Corporate income tax, Personal income tax, South Africa, India, subcontracting, secondment, OECD Model Tax Convention, Double Tax Agreements and Permanent Establishment.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Commerce (Specialising in Taxation) Johannesburg, 2017
Keywords: International business enterprises--Taxation--Law and legislation; Business enterprises, Foreign--Taxation--Law and legislation; Double taxation